2010
DOI: 10.1097/rct.0b013e3181ddbbc0
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Coronary Stents With 64-Row Multidetector Computed Tomography

Abstract: Metal artifacts cause overlooking of nonsignificant stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Four-and 16-slice CT were of limited value in the assessment CISR owing to frequent incidence of stent-related artifacts and cardiac motion, which significantly decreased the accuracy and lead up to 36% stents to be considered as inaccessible in 16-slice CT (5,32). With the application of 64-slice CT, some of these limitations have been partially overcome due to the improvement of temporal and spatial resolutions (33,34). A previous meta-analysis performed by Carrabba et al (6) reported that 64-slice CT can reach weighted SEN of 86% and SPE of 93% in the detection of CISR compared to ICA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four-and 16-slice CT were of limited value in the assessment CISR owing to frequent incidence of stent-related artifacts and cardiac motion, which significantly decreased the accuracy and lead up to 36% stents to be considered as inaccessible in 16-slice CT (5,32). With the application of 64-slice CT, some of these limitations have been partially overcome due to the improvement of temporal and spatial resolutions (33,34). A previous meta-analysis performed by Carrabba et al (6) reported that 64-slice CT can reach weighted SEN of 86% and SPE of 93% in the detection of CISR compared to ICA.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, a major problem concerning assessment of stents defined as beamhardening artifacts could result in artificial luminal narrowing, decreased intraluminal attenuation values, and make stents appear larger than they actually are (36). Second, the presence of metal within the coronary stent struts can lead to high-density artifacts (blooming artifacts), which can potentially decrease the accuracy in interpreting ISR and therefore can became one of the important causes of a false-positive result or diagnosis (33,36). Furthermore, our study reported that stents with smaller diameters (<3 mm) might have had a negative influence on CISR diagnosis compared to bigger stent diameters, mainly because smaller stent diameters are more difficult to visualize in lumen in MSCT (25,32).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…First of all, a major problem concerning assessment of stents defined as blooming (beam hardening) artifacts could result in artificial luminal narrowing, decreased intraluminal attenuation values, and make stents appear larger than they actually are . Second, the presence of metal within the coronary stent struts can lead to high‐density artifacts, which can potentially decrease the accuracy in interpreting CISR and therefore became one of the important causes of false‐positive result or diagnosis . Third, our study reported that stents with smaller diameters (<3 mm) might have had a negative influence on CISR diagnosis compared with bigger stents diameters, mainly because smaller stent diameters are more difficult to be visualized in lumen in DSCTA .…”
Section: Discussionmentioning
confidence: 84%
“…Four‐ and 16‐slice CTA were of limited value in assessing CISR owing to frequent incidence of stent‐related artifacts and cardiac motion, which significantly decrease the accuracy and lead up to 36% stents to be considered as inaccessible in 16‐slice CT . With the application of 64‐slice CT, some of these limitations have been partially overcome due to the improvement of temporal and spatial resolutions . A previous meta‐analysis performed by Carrabba et al reported that 64‐slice CT can reach weighted SEN of 86% and SPE of 93% in the detection of CISR as compared to ICA.…”
Section: Discussionmentioning
confidence: 99%
“…Better temporal and spatial resolution permit a negative predictive value (NPV; 90–100%) [ 54 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ]. In comparison to earlier systems, the new generation MSCT overcomes the restrictions that were caused due to low resolution [ 67 , 68 ].…”
Section: In-stent Restenosis Monitoringmentioning
confidence: 99%